Slovar členkov kot živa vez med besedilom in slovarjem - Žele, Andreja (Slavia Centralis, 2020)
DICTIONARY OF PARTICLES AS A LIVING LINK BETWEEN THE TEXT AND DICTIONARYThis article posits a theoretical-practical depiction of the particle as a dynamic function word and sentence modifer. The research brings together and provides commentary on contemporary linguistic assumptions about the particle and the practical, or lexical, display of how particles are used in Slovenian texts.
Keywords: particle; function word; mood and connecting roles of particles; text; dictionary